2003
DOI: 10.1111/j.1755-0238.2003.tb00266.x
|View full text |Cite
|
Sign up to set email alerts
|

ABA during reproductive development in non-irrigated grapevines (Vitis vinifera L. cv. Tempranillo)

Abstract: In grapevines, stomatal aperture decreases after a mid‐morning peak during summer days. Afternoon stomatal closure increases in non‐irrigated plants as water limitation progresses, which suggests the involvement of abscisic acid (ABA) in the control of stomatal aperture. The objective of this work was to study the seasonal and diurnal time‐courses of CO2 assimilation rate, leaf conductance, leaf water potential +, and ABA concentration in xylem sap, leaves, flowers and berries in non‐irrigated field‐grown Temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 34 publications
4
28
1
Order By: Relevance
“…Merlot during ripening. ABA accumulates during the colour change period, in agreement with other works (Antonin et al, 2003;DaPeng et al 1997;Gagné et al, 2006), suggesting a central role of ABA in triggering veraison and ripening. This accumulation is clearly related to the change of skin coloration.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Merlot during ripening. ABA accumulates during the colour change period, in agreement with other works (Antonin et al, 2003;DaPeng et al 1997;Gagné et al, 2006), suggesting a central role of ABA in triggering veraison and ripening. This accumulation is clearly related to the change of skin coloration.…”
Section: Discussionsupporting
confidence: 91%
“…During grape ripening, the source of synthesis of ABA is doubtful. Antonin et al (2003) suggested that, during ripening, the majority of ABA is transported from leaves to berries where it accumulates. In contrast, Okamoto et al (2004) reported that ABA levels were not always dependent on leaf ABA levels during ripening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers suggest that berry ABA is made in the leaves and is transported to the ripening berry where it accumulates (Antolin et al, 2003). The increase in ABA level at veraison and the possible influence on sugar and anthocyanin accumulation indicated that ABA may be a crucial mediator of the ripening process in grapes and need further research.…”
Section: 2c Leaf Characteristics For the Second Pickingmentioning
confidence: 99%